PENINGKATAN KEPERCAYAAN DIRI SISWA DALAM KOMUNIKASI SAINS MELALUI MODEL PEMBELAJARAN INKUIRI TERBIMBING DI SEKOLAH DASAR - Riris Wahyuni; Mufarizuddin; Sumianto; Melvi Lesmana Alim; Muhammad Syahrul Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of students' self-confidence in expressing opinions and using scientific language in class V of UPT SDN 015 Tanjung Rambutan. One solution to overcome this problem is through the use of the guided inquiry learning model. The aim of this study is to present the improvement of students' self-confidence in science communication through the guided inquiry learning model for class V students at UPT SDN 015 Tanjung Rambutan. The research method used is Classroom Action Research (CAR), which was carried out in two cycles, each conducted twice. Each meeting consisted of four stages: planning, implementation, observation, and reflection. The research was conducted in June 2025. The research subjects were class V students totaling 12 students, consisting of 6 boys and 6 girls. The data collection techniques included observation sheets, interviews, and documentation. The research instruments included teacher and student activity observation sheets. The data analysis techniques used were qualitative and quantitative data analysis. The results of the study showed that students' self-confidence in science communication improved in each meeting. The percentage results in Cycle I, Meeting I reached (50%), Meeting II increased to (66%), then in Cycle II, Meeting I (75%) and in Meeting II reached (83%). Thus, it can be concluded that the guided inquiry learning model can improve students' self-confidence in science communication, particularly in the topic of energy sources and their changes in class V of UPT SDN 015 Tanjung Rambutan.